On the Road to a Dialect Dictionary of Khanty Postpositions - Schön, Zsófia (Septentrio Conference Series, 2015)
This paper aims to present the first steps of a corpus based dialect dictionary of postpositions in several Khanty dialects and subdialects. Based primarily on specifically elicitated data from more than fifty informants, this ongoing project focuses not only on the semantic properties of this part of speech in Khanty, but also on the morphology and combinatorics as exhibited by (sub)dialectal microvariation. Special attention is paid to two of the Northern dialects – Kazym and Shuryshkary Khanty – and to one of the Eastern dialects – Surgut Khanty. The lexicon entries have been compiled according to TEI P5 guidelines in XML format, while the corpus data is stored in a MySQL database. A web application combining the lexicon with the corpus data, sound files, annotations and metadata is currently under construction. As a multilingual dialect dictionary of Khanty postpositions, this project hopes to fill a gap in current research on Khanty: namely the lack of easily accessible digital dictionaries. It is designed to be a pilot project for forthcoming digital Khanty dictionaries.